Reproductive biology of the mudskipper Boleophthalmus boddarti in Soc Trang - Quang, Dinh Minh; Tra Giang, Nguyen Thi; Kieu Tien, Nguyen Thi (Academia Journal of Biology, 2016)
The mudskipper Boleophthalmus boddarti is an amphibious fish widely distributed in the mudflat regions in Asia, but its reproductive biology was poorly stydied. This study was conducted in the Tran De, Soc Trang, Vietnam, from March 2013 to February 2014, to investigate reproductive parameters of B. boddarti. Data analysis based on a total of 360 collected fish (188 females and 172 males) suggest that the sex ratio of this mudskipper was not significantly different between dry and wet seasons. This fish was a multiple reproducer and spawned in the wet season with a peak spawning in three main months of this season (August to October) as difference stages of oocytes were observed in the ovaries. The male B. boddarti released sperms during the reproductive season since different type of spermatogonia were found in stage V testis sections. This fish reached 11.52 cm total length at first sex maturation and was high fecundity (9,800-33,800 eggs), indicating a possible adaptation of this species to the monsoonal climate. The understanding of the reproductive biology of B. boddarti provides useful knowledge of its reproductive adaptation to the mudflat toward sustainable management in the study region.